The influence of concomitant antidepressant and antipsychotic medication on antidepressant effect and seizure duration of electroconvulsive therapy - Mohamad, Sara; Trumm, Samuel; Treskatsch, Sascha; Drevs, Alisha; Bajbouj, Malek; Wiedemann, Leonardo (Frontiers in Psychiatry, 2024)
Background: A significant proportion of patients with a depressive disorder show resistance to pharmacological and psychotherapeutic antidepressant treatments. Electroconvulsive therapy (ECT) is still one of the most effective treatment methods, especially in the acute phase. In everyday clinical practice, this usually accompanies pharmacological treatment. It has been shown that pharmacological treatment following acute ECT treatment reduces the rate of relapses. However, the effect of various antidepressants (AD) and antipsychotics (AP) on the effect during the course of ECT has rarely been investigated Methods: In this retrospective chart review study, the data of 104 depressive patients treated with ECT were examined. We analysed the influence of concomitant administration of AD and AP or no psychotropic medication on the effect of ECT using the Montgomery-Åsberg Depression Rating Scale (MADRS). We further analysed the influence of the ADs Bupropion, Venlafaxine and Sertraline or no AD as well as the influence of augmentation with Aripiprazole or Quetiapine or Olanzapine. Results/discussion: Psychotropic medication did not have an impact on antidepressant efficacy of ECT as measured with the MADRS scores. Also, the comparison between the antidepressant or antipsychotic medications themselves did not show any significant difference. But we found a significantly different seizure duration depending on the antidepressant substance that patients received during ECT (p = .008). ECT treatment itself led to a highly significant reduction of 13.3 points in the MADRS (p < .001).Taken together, our study underlines that concomitant psychotropic medication while doing electroconvulsive therapy does not bare the risk of prolonged seizure duration nor does it reduce the effectiveness of ECT. To the best of our knowledge, this study is the first to examine the effect of treatment with antidepressants in combination with antipsychotics while doing ECT. In the light of our results, this combination therapy is safe and effective. Baring in mind the delay in onset of antidepressant action of medication and the importance of antidepressant medication for relapse prevention, this study further supports the recommendation that psychotropic medication should be given in adjunction to ECT.